Management of neurofibromatosis type 1-associated plexiform neurofibromas. Issue 11 (3rd June 2022) - Fisher, Michael J; Blakeley, Jaishri O; Weiss, Brian D; Dombi, Eva; Ahlawat, Shivani; Akshintala, Srivandana; Belzberg, Allan J; Bornhorst, Miriam; Bredella, Miriam A; Cai, Wenli; Ferner, Rosalie E; Gross, Andrea M; et al.
Abstract: Plexiform Neurofibromas (PN) are a common manifestation of the genetic disorder neurofibromatosis type 1 (NF1). These benign nerve sheath tumors often cause significant morbidity, with treatment options limited historically to surgery. There have been tremendous advances over the past two decades in our understanding of PN, and the recent regulatory approvals of the MEK inhibitor selumetinib are reshaping the landscape for PN management. At present, there is no agreed upon PN definition, diagnostic evaluation, surveillance strategy, or clear indications for when to initiate treatment and selection of treatment modality. In this review, we address these questions via consensus recommendations from a panel of multidisciplinary NF1 experts.